1999
DOI: 10.1074/jbc.274.14.9283
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinol:Cytochrome c Oxidoreductase

Abstract: The effects of inhibitors on the reduction of the bisheme cytochrome b of ubiquinol: cytochrome c oxidoreductase (complex III, bc 1 complex) has been studied in bovine heart submitochondrial particles (SMP) when cytochrome b was reduced by NADH and succinate via the ubiquinone (Q) pool or by ascorbate plus N,N,N,Ntetramethyl-p-phenylenediamine via cytochrome c 1 and the iron-sulfur protein of complex III (ISP). The inhibitors used were antimycin (an N-side inhibitor), ␤-methoxyacrylate derivatives, stigmatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 27 publications
6
40
0
Order By: Relevance
“…Although, on the basis of the evaluated heteroplasmy of the patients' mitochondrial samples, nearly 20% of the F 1 F 0 complexes are active, the ATP synthesis rate decreased by a factor of nearly 20 (on the mean basis, 5% residual synthesis activity). Our expected result was 20% residual activity or higher if the greater driving force for each individual normal F 1 F 0 complex was taken into account, as according to Hatefi (6) and Matsuno-Yagi and Hatefi (34). However, the observed lower than expected ATP synthesis rate might be only apparent, for instance, given that the mutated mtDNA T8993G Mutation and F 1 F 0 -ATPase ActivityF 1 F 0 complexes could still fully exert the ATP hydrolysis activity.…”
Section: Resultssupporting
confidence: 50%
“…Although, on the basis of the evaluated heteroplasmy of the patients' mitochondrial samples, nearly 20% of the F 1 F 0 complexes are active, the ATP synthesis rate decreased by a factor of nearly 20 (on the mean basis, 5% residual synthesis activity). Our expected result was 20% residual activity or higher if the greater driving force for each individual normal F 1 F 0 complex was taken into account, as according to Hatefi (6) and Matsuno-Yagi and Hatefi (34). However, the observed lower than expected ATP synthesis rate might be only apparent, for instance, given that the mutated mtDNA T8993G Mutation and F 1 F 0 -ATPase ActivityF 1 F 0 complexes could still fully exert the ATP hydrolysis activity.…”
Section: Resultssupporting
confidence: 50%
“…Bovine heart mitochondria were kindly provided by Prof. Chang-An Yu (Oklahoma State University, Stillwater, OK), and bovine heart SMP were prepared according to Ref. 26. Piericidin A 1 was a generous gift from Prof. Dale.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, the occurrence of a membrane potential-dependent back-reaction through the Qi site has been documented in the case of bc 1 complexes (51)(52)(53)(54). The presence of this backreaction has suggested that the interheme electron transfer is a reversible process.…”
Section: Mechanism Of the Membrane Potential Effect On Plastoquinone mentioning
confidence: 99%